2022
DOI: 10.3389/fonc.2022.856231
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Classifying High- and Low-Grade Gliomas: A Systematic Review and Quality of Reporting Analysis

Abstract: ObjectivesTo systematically review, assess the reporting quality of, and discuss improvement opportunities for studies describing machine learning (ML) models for glioma grade prediction.MethodsThis study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses of Diagnostic Test Accuracy (PRISMA-DTA) statement. A systematic search was performed in September 2020, and repeated in January 2021, on four databases: Embase, Medline, CENTRAL, and Web of Science Core Collection. Publications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Multiple works demonstrated high accuracy with use of ML for tumor segmentation, identification of images with brain tumors from other pathologies, glioma grade and molecular subtype prediction, differentiation of gliomas from lymphoma or brain metastases. These results suggest that clinical implementation of these algorithms is imminent and will be seen in the clinical practice in the next few years (Subramanian et al, 2021;Afridi et al, 2022;Avery et al, 2022;Bahar et al, 2022;Cassinelli Petersen et al, 2022;Jekel et al, 2022;Tillmanns et al, 2022). The next frontier in neuro-oncology imaging is identification of clinical applications of ML algorithms in clinical practice and determining the aspects of clinical care that can be improved with predictions that can be generated by these algorithms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple works demonstrated high accuracy with use of ML for tumor segmentation, identification of images with brain tumors from other pathologies, glioma grade and molecular subtype prediction, differentiation of gliomas from lymphoma or brain metastases. These results suggest that clinical implementation of these algorithms is imminent and will be seen in the clinical practice in the next few years (Subramanian et al, 2021;Afridi et al, 2022;Avery et al, 2022;Bahar et al, 2022;Cassinelli Petersen et al, 2022;Jekel et al, 2022;Tillmanns et al, 2022). The next frontier in neuro-oncology imaging is identification of clinical applications of ML algorithms in clinical practice and determining the aspects of clinical care that can be improved with predictions that can be generated by these algorithms.…”
Section: Discussionmentioning
confidence: 97%
“…Future work will include implementation of advanced algorithms, such as nnUNET which show higher DSC scores. Currently machine learning in medical imaging is a hot topic with a large spike in publications starting in 2017 (Subramanian et al, 2021;Afridi et al, 2022;Avery et al, 2022;Bahar et al, 2022;Cassinelli Petersen et al, 2022;Jekel et al, 2022). Multiple works demonstrated high accuracy with use of ML for tumor segmentation, identification of images with brain tumors from other pathologies, glioma grade and molecular subtype prediction, differentiation of gliomas from lymphoma or brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In our systematic review of 85 published ML studies developing models for image-based glioma grading, we found SVM and CNN to have mean accuracies of 90% and 91%, respectively [ 51 ]. Mean accuracies for these algorithms were similar across classification tasks regardless of whether the classification was binary or multi-class (e.g., 90% for the 24 studies whose best models performed binary classification of grades 1/2 vs. 3/4 compared to 86% for the 5 studies classifying grade 2 vs. 3 vs. 4).…”
Section: Algorithms For Glioma Grade Classificationmentioning
confidence: 99%
“…Similar findings have been reported for glioma grade prediction literature. In our prior study conducting a TRIPOD analysis of more than 80 such model development studies, we report a mean adherence rate to TRIPOD of 44%, indicating poor quality of reporting [ 51 ]. Areas for improvement included reporting of titles and abstracts, justification of sample size, full model specification and performance, and participant demographics, and missing data.…”
Section: Challenges In Image-based ML Glioma Gradingmentioning
confidence: 99%
See 1 more Smart Citation